Development of Innovative Assessment Methods in the Context of Modern Learning - Nurazizah Aliah; Nurasia Natsir; Zulkhaeriyah Zulkhaeriyah (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to develop innovative assessment methods in the context of modern Learning. In today's digital age, traditional approaches to learning assessment are often no longer sufficient to holistically assess student progress and success. Thus, this study proposes a more innovative and comprehensive assessment method that uses modern technology and considers students' individual needs. This study identified and tested promising new assessment tools and techniques through pilot projects, such as digital portfolios, peer assessment, and realistic simulations. In addition, this study also explores how technologies such as learning analytics can be used to provide more meaningful and timely feedback to students and teachers. The results of this study indicate that this innovative assessment method can improve student engagement, comprehension, and learning outcomes. These findings also suggest that teachers and educators can use technology and data to make more informed decisions about how to develop and implement assessment strategies. In conclusion, developing innovative assessment methods in modern learning environments is essential for more inclusive, adaptive, and practical education. By integrating technology and new assessment approaches, this research significantly contributes to our understanding of creating more effective and engaging assessment systems in this digital era.